Obstetric referral practices and health system factors in public health centres of Addis Ababa, Ethiopia: A mixed-methods study - Amaha Haile Abebe; Rose Mmusi-Phetoe (PLOS One, 2026)
Objective To determine the rate of obstetric referral and explore contextual factors influencing referral practices in public health centres of Addis Ababa, Ethiopia. Design Explanatory sequential mixed-methods study. Setting and period Fifty public health centres in the Addis Ababa City Administration, January–April 2021. Methods Delivery and referral registers from 50 health centres were reviewed retrospectively for 12 months (8 July 2019–7 June 2020). Facility observations and interviews with maternity unit heads were conducted in all selected centres. In-depth interviews were conducted with 20 midwives and 13 health centre managers. Quantitative data were analysed descriptively, and qualitative data were analysed thematically using Colaizzi’s method. Results Only 13 (26%) of the 50 health centres have met all eight standards assessed for functionality of the referral system. The main gaps of the referral system were a lack of ambulance (12%), absence of formal agreement with referral centers, and lack of timely case-by-case feedback from referral centers(64%). The overall obstetric referral rate was 32%, with substantially higher referral rates in health centers without caesarean section (CS) services compared with those providing CS (39% vs 21%). Qualitative findings indicated that high referral rates were associated with limitations in the predictive capacity of the partograph, variability in providers’ clinical skills, and risk-averse practices driven by accountability concerns related to maternal and perinatal outcomes. Conclusion Improving functionality of referrals and reducing unnecessarily high referrals requires adopting and training providers on the new WHO labour guide and partograph, improving referral feedback, and clarifying accountability mechanisms.